Neurophysiology in Alzheimer's Disease and Dementia - Davide Vito Moretti (Frontiers Research Topics, 2016)
Alzheimer's disease (AD) and dementia are the most common neurodegenerative disorder. Since the number of individuals with AD and dementia is expected to increase considerably in the near future, reliable treatment and diagnosis are critical. EEG and neurophysiological technique could be used as a cost-effective screening tool for early detection and diagnosis in the Mild Cognitive Impairment (MCI) stage. The aim in neurophysiology research is to develop signal processing methods that improve the specificity for diagnosing dementia; we wish to discover signal features that not only significantly differ in AD patients, but also allow us to reliably separate AD patients and control subjects. This approach is valuable for clinical purposes (as diagnostic tool for dementia), and it also more fundamentally contributes to a better understanding of brain dynamics of MCI patients. Finally, the development of neurophysiological biomarker could be useful in monitoring pharmacological treatments. The main focus of this special issue will be on the most recent developments and ideas in the field of EEG and neurophysiology which will enable us to extract features that improve the specificity for diagnosing AD and dementia.